Implementation of Dynamic Governance in Improving Service Quality (Case Study: Palembang City Public Service Mall) - Bianto Bianto; Nurmah Semil; Sena Putra Prabujaya (JURNAL ECONOMINA, 2026)
Improving public service quality has become a key objective of bureaucratic reform, encouraging governments to adopt adaptive governance through the Dynamic Governance approach. This study aims to analyze the implementation of Dynamic Governance in improving service quality at the Public Service Mall (Mal Pelayanan Publik/MPP) of Palembang City and to identify the factors supporting its implementation. A qualitative descriptive approach was employed using interviews, observations, and documentation. Data were analyzed based on Neo and Chen's Dynamic Governance framework, consisting of Thinking Ahead, Thinking Again, and Thinking Across. The findings reveal that Dynamic Governance has contributed to service quality improvement through technology-based service innovation, continuous service evaluation, and strengthened inter-agency coordination and collaboration. However, challenges remain, including limited digital system integration, differences in institutional systems, and insufficient human resource capacity. Supporting factors include competent human resources, inter-agency collaboration, and a supportive regulatory framework. The study concludes that Dynamic Governance contributes to improving public service quality at the Palembang Public Service Mall, while further efforts are needed to strengthen digital transformation, service integration, and the capacity of public officials.